Novel Vehicles For Drug Delivery In Atopic Dermatitis: A Narrative Review - Farkouh, Christopher; Anthony, Michelle; Abdi, Parsa; Natalia Santiago; Farkouh, Matthew (Dermatology Practical & Conceptual, 2023)
Introduction: Atopic dermatitis (AD) causes dry and itchy skin and inflammation that severely impairs the quality of life of affected children and adults. While topical glucocorticosteroid application is typically the first-line treatment of choice, steroid treatment is associated with side effects and, increasingly, patient concerns about prolonged use. Novel drugs and drug delivery vehicles are required for patients with AD. Objective: To summarize the current literature on novel topical agents for atopic dermatitis and novel delivery vehicles. Methods: A literature search was conducted, and a narrative review was compiled to summarize recent evidence. Results: Novel topical drugs approved or in late-phase clinical trials for the treatment of AD include the Janus kinase inhibitor ruxolitinib, the phosphodiesterase-4 inhibitors crisaborole, and roflumilast, and the aryl hydrocarbon receptor activator tapinarof. While current topical drugs for AD are delivered via creams, ointments, gels, and related vehicles, novel delivery approaches such as electrospun patches, sprays, liposomes, nanoparticles, and lasers are being developed to enhance transdermal delivery, reduce side effects, and increase treatment adherence. Conclusion: Topical application of creams or ointments is currently the predominant vehicle for the delivery of atopic dermatitis drugs. In vitro studies on novel vehicles show promising results to overcome the issues associated with topical delivery. Still, these findings have to be corroborated by controlled studies with human patients in the future.